TEACHING STRATEGIES USED IN ESP CLASSES - Dewi Kadek Maya Cyntia; Surya I Gede Galang; Susanta I Putu Agus Endra (Universitas Pendidikan Ganesha, 2019)
This study aimed to describe teaching strategies implemented by lecturers in teaching English of continuing program students at STIKES Bali. Descriptive qualitative design use used. There were 2 respondents involved in this study which were lecturers who taught English in continuing program at STIKES Bali. The data were collected by using observation sheet and interview guide. The data were analyzed descriptively according to descriptive qualitative design. The finding showed that there were 5 teaching strategies from 7 teaching strategies proposed implemented by lecturer such as Direct Instruction, Discussion, Group Work, Co-operative Learning and Performance Activity. Direct Instruction and Discussion were the most teaching strategies that chosen by English lecturers. Teaching strategies were implemented according to the topics and characteristics of the students. Choosing the right teaching strategy is very important in teaching English, especially in continuing program students at STIKES Bali. English lecturers in STIKES Bali are expected to implement more and appropriate teaching strategies to improve the quality of teaching and learning process.